Anti-caspase-3 preconditioning increases proinsulin secretion and deteriorates posttransplant function of isolated human islets. - Brandhorst, D; Brandhorst, H; Maataoui, V; Maataoui, A; Johnson, P (2013)
Human islet isolation is associated with adverse conditions inducing apoptosis and necrosis. The aim of the present study was to assess whether antiapoptotic preconditioning can improve in vitro and posttransplant function of isolated human islets. A dose-finding study demonstrated that 200 μmol/L of the caspase-3 inhibitor Ac-DEVD-CMK was most efficient to reduce the expression of activated caspase-3 in isolated human islets exposed to severe heat shock. Ac-DEVD-CMK-pretreated or sham-treated islets were transplanted into immunocompetent or immunodeficient diabetic mice and subjected to static glucose incubation to measure insulin and proinsulin secretion. Antiapoptotic pretreatment significantly deteriorated graft function resulting in elevated nonfasting serum glucose when compared to sham-treated islets transplanted into diabetic nude mice (p < 0.01) and into immunocompetent mice (p < 0.05). Ac-DEVD-CMK pretreatment did not significantly change basal and glucose-stimulated insulin release compared to sham-treated human islets but increased the proinsulin release at high glucose concentrations (20 mM) thus reducing the insulin-to-proinsulin ratio in preconditioned islets (p < 0.05). This study demonstrates that the caspase-3 inhibitor Ac-DEVD-CMK interferes with proinsulin conversion in preconditioned islets reducing their potency to cure diabetic mice. The mechanism behind this phenomenon is unclear so far but may be related to the ketone CMK linked to the Ac-DEVD molecule. Further studies are required to identify biocompatible caspase inhibitors suitable for islet preconditioning.